Methodology of the Evaluation of “Komuniti Sihat Pembina Negara-Plus” (KOSPEN Plus) Programme among Workers in Malaysia (Phase 1) - Lim Kuang Kuay; Mohd Shaiful Azlan Kassim; Hasimah Ismail; Abdul Aziz Harith; Chan Ying Ying; Zalilah Abdullah; Low Lee Lan; Munirah Ismail; Mohd Azahadi Omar (Budapest International Research and Critics University, 2021)
In 2016, the Ministry of Health (MOH) Malaysia has introduced a new programme to prevent and reduce the occurrence of non-communicable diseases (NCDs) as well as related risk factors in the work place environment known as KOSPEN Plus. This study aims to evaluate the awareness and perception of KOSPEN Plus programme after 3 years of implementation in MOH health facilities, government and private agencies in Malaysia. A cross sectional study design was employed in the study. All health facilities, government and private agencies which had implemented KOSPEN Plus programme between 2016 and 31 December 2018 in all states in Malaysia were invited to participate in the study. The computer assisted self-interview (CASI) using the pre-tested self-administered questionnaire in the electronic form was used. A total of 362 health facilities, government and private agencies which had implemented KOSPEN Plus programme was involved in this study. Overall, more than 80% of facilities/agencies in this study implemented six out of the eight scopes of KOSPEN Plus. The survey was planned with the goal of obtaining data to support the Ministry of Health in reviewing the present health activities related to workers health in Malaysia and make necessary improvement to the programme.